Diagnosing and distinguishing rotor eccentricity from partial demagnetisation of interior PMSM based on fluctuation of high‐frequency d‐axis inductance and rotor flux. Issue 7 (1st August 2017) - Liu, Zijian; Huang, Jin; Li, Bingnan
Abstract : An appropriate and complete mathematical modelling approach is developed for an interior permanent magnet synchronous motor (PMSM) with general eccentricity. The relationships between air‐gap eccentricity and simulated inductances in different coordinate frames are analysed in depth. Then, an analytical high‐frequency inductance model of the interior PMSM with rotor eccentricity is developed. Based on this model, an online diagnostic approach is proposed, which includes estimation of the high‐frequency d ‐axis inductance and permanent magnet (PM) flux. Thus the rotor eccentricity and PM partial demagnetisation can be detected and distinguished. Experimental results validate the proposed theory and fault diagnosis approach. Finally, an effective and reliable eccentricity indicator is presented. It is shown that analysis of the essential sources of fault characteristics facilitates motor fault diagnosis.